Enforcing corporate citizenship through social media : the role of shares, clicks, and likes in sustainability communications - Poutanen, Jenni (2018)
This research presents how individual social media users perceive social media as a part of sustainability communications and examines whether these individuals consider organizational legitimacy and brand image being enforced through social media communications. During the recent years, web-based communications, especially the exponentially increased use of social media, has altered the communicational field tremendously, and whereas print media once stood, internet has now taken over and created an illusion of a panopticon. This study is built on the assumption that social media as one of the most dominant communication tools can be utilized in enforcing corporate legitimacy and sustainability due to its presumably evident transparency and ability to act in a role of a whistleblower and can therefore be considered as an essential part of sustainability communications. The study is based on analyzing perceptions of individual social media users, gained through a questionnaire distributed via different social media channels. The analysis was based on examining firstly the general information of the respondents; gender, age, educational and professional background, and social media usage, after which these attributes were cross-analyzed with the claims revealing how the respondents considered the relationship between social media, sustainability and corporate legitimacy. This aimed to examine the dependencies between the background information of the respondents and their perceptions and reveal whether there are dominant factors present that would affect the overall analysis. Though the study supports the research assumption, the analysis revealed that there is a strong correlation between the background of an individual and the relationship of how social media is perceived in sustainability. This thesis provides essential knowledge for corporations focusing on sustainability communications, and moreover, contributes to further research by providing initial data, and establishing grounds for continuing more in- depth analysis regarding the Holistic Stakeholder Mapping Model and legitimation theory.